1965
DOI: 10.1210/jcem-25-1-95
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Urinary Testosterone by Chromatography and Colorimetry: Findings in Normal Subjects and in Patients with Endocrine Diseases1

Abstract: In this method for measuring conjugated urinary testosterone, testosterone-4-14 C is added to an aliquot of urine to correct for subsequent losses and an ethyl ether extract is then chromatographed in 2 Zaffaroni systems prior to chromic oxide oxidation of testosterone to A 4 -androstene-3,17-dione. A third Zaffaroni system confirms the completion of oxidation and purifies the steroid before a final fourth chromatography in a Bush system. Quantitation is carried out by a modified micro Zimmermann reaction. Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1966
1966
1974
1974

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Since testosterone is the most potent natural androgenic hormone and the adrenal is capable of synthesizing testosterone (4), increased secretion of this steroid has been suggested as the responsible mechanism. This hypothesis is supported by the demonstration of increased urinary excretion (5)(6)(7)(8)(9)(10)(11), plasma concentration (10,(12)(13)(14), and production rate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) of testosterone in patients with congenital adrenal hyperplasia. However, recent work by Korenman and Lipsett (15) and Horton and Tait (16) indicates that the weak androgen, androstenedione (androst-4-ene-3, 17- ther demonstrated that almost two-thirds of blood testosterone in the normal female is derived from blood androstenedione.…”
Section: Introductionmentioning
confidence: 87%
“…Since testosterone is the most potent natural androgenic hormone and the adrenal is capable of synthesizing testosterone (4), increased secretion of this steroid has been suggested as the responsible mechanism. This hypothesis is supported by the demonstration of increased urinary excretion (5)(6)(7)(8)(9)(10)(11), plasma concentration (10,(12)(13)(14), and production rate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) of testosterone in patients with congenital adrenal hyperplasia. However, recent work by Korenman and Lipsett (15) and Horton and Tait (16) indicates that the weak androgen, androstenedione (androst-4-ene-3, 17- ther demonstrated that almost two-thirds of blood testosterone in the normal female is derived from blood androstenedione.…”
Section: Introductionmentioning
confidence: 87%
“…Normal values for the excretion of testosterone glucuronide have been obtained in Addison's disease (Ibayashi et al, 1964;Vermuelen, 1966), and consistently raised values of excretion and plasma-testosterone level and production have been found in congenital adrenal hyperplasia (Burger et al, 1964;Futterweit et al, 1964;Casey, 1965 ;Korenman et al, 1965;Lim and Dingman, 1965 ;Rosner et al, 1965;Degenhart et at., 1966) but the correlation with 17-oxosteroid excretion is not close; there is in this condition good suppression of testosterone with corticosteroid. Few observations are available in Gushing's syndrome with adrenal hyperplasia, but urinary testosterone glucuronide is increased (Ibayashi et al, 1964Vermuelen, 1966) and a high level of testosterone has been observed in the adrenal vein (Hudson et at., 1963) and a low level in the peripheral plasma of such a patient after adrenalectomy .…”
Section: Dhasmentioning
confidence: 95%
“…A few series of patients with CAH have been published ; rates of production and excretion of testosterone were determined and were found to be elevated [25,36]. KORENMAN et al [21] describe a case with only a slightly increased testosterone UPR and one case with an elevated UPR.…”
Section: Discussionmentioning
confidence: 99%